VD_FINDINFO AM 4/09 - 18/2011 vom 10. März 2011 - VD Tribunal cantonal (2011)
LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, MALADIE, DÉFAUT ESTHÉTIQUE | 25 al. 1 LAMal, 25 al. 2 let. a LAMal, 32 LAMal, 33 al. 1 LAMal, 33 al. 5 LAMal, 34 LAMal, 33 let. a OAMal, 33 let. c OAMal, 1 OPAS